Employee perception of grievance management with its link to workplace justice: City of Harare Council. Harare - Nyangwaira, Nerissa R. (Midlands State University, 2017)
The study was based on employee perception of grievance management with its link to workplace justice, a case study of City Of Harare Council. The research was qualitative in nature; henceforth descriptive research design was employed. Moreover the research was carried out with seventeen participants to represent the population and data was collected using face to face in-depth interviews. To add more the data collected was presented using verbatim and then the results were ultimately analysed using thematic analysis method. Diligently the results of the study posed that the employees are dissatisfied with the grievance management system hence they perceived that there is no workplace justice at the organization. The main findings were that employees at City of Harare Council have multiple grievances yet they are not resolved effectively, organizational justice is not promoted hence most of the employees are deeply aggrieved. Finally the conclusions concerning the findings of the study and recommendations were made.